Ethiopia Alive & Thrive Endline Survey 2014: Volunteer Community Health Promoters - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the volunteer community health promoters (VCHP) survey that was conducted to gather data for the endline part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions (CBI), delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of infant and young child feeding (IYCF) practices in two regions where the integrated family health program (IFHP) operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative funded by the Bill & Melinda Gates Foundation to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The impact evaluation of the A&T Ethiopia community-based intervention and mass media activities includes the 2010 baseline and 2014 endline surveys and a smaller-scale 2013 process evaluation survey. Together, these studies generate answers to one of the major learning objectives for the overall initiative: how A&T interventions achieve their impact. The Ethiopia endline survey applied five separate questionnaires that aimed to capture elements along the program impact pathways. These instruments included a household questionnaire, a community questionnaire and 3 frontline health workers questionnaires, which are: - health extension workers (HEW) questionnaire - supervisors of HEWs questionnaire - volunteer community health promoters questionnaire. Volunteers include all kind of volunteers working on promoting health and nutrition such as volunteer community health promoter (VCHP), health development agent (HAD), development agent (DA), health animator etc. The volunteer community health promoters (VCHP) questionnaire, along with the other two FLW questionnaires, aimed at assessing four major issues: (1) frequency of interactions between FLWs and mothers/caregivers and modes of interactions; (2) content of the interactions between FLWs and mothers/caregivers, especially discussions about IYCF messages and the time spent on IYCF-related discussions; (3) IYCF knowledge and training received by FLWs; and (4) FLWs’ motivation and satisfaction about their jobs. These are captured by questions on perceptions related to workload and level of job satisfaction. This is particularly important to capture among volunteers who receive no salary.